Santri Service Program Management Produces Collaborative Soft Skills: Manajemen Program Pengabdian Santri Menghasilkan Soft Skill Kolaboratif - Al mahbuba, Abidatul qoyyum; Arifin, Imron; Sumarsono, Raden Bambang; Imron, Ali (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Global disruption has shifted success determinants from academic intelligence toward soft skills such as communication, leadership, and collaboration. Specific Background: Islamic boarding school graduates often exhibit disparities between intellectual competence and practical social abilities required in dynamic work and social environments. Knowledge Gap: Limited structured integration of community service within educational systems constrains optimal soft skill formation among students. Aims: This study examines the management of santri community service programs as a structured educational mechanism for developing soft skills through experiential learning. Results: Findings demonstrate that systematic management encompassing planning, organization, implementation, and evaluation functions as a living laboratory where teaching, learning, and service integration cultivate communication, leadership, teamwork, and problem-solving competencies. The program also aligns with waqf-based institutional philosophy, reinforcing sustainability and collective responsibility. Novelty: The study highlights a comprehensive management framework that integrates experiential learning with institutional philosophy to produce holistic student development. Implications: The findings provide a scalable reference for Islamic education systems to structure community service programs as a continuous, experience-based learning model that strengthens social competencies and institutional sustainability. Highlights• Systematic program governance builds integrated experiential learning environments• Service-based activities cultivate leadership, communication, and teamwork competencies• Waqf-oriented framework supports institutional continuity and collective responsibility KeywordsProgram Management; Community Service; Soft Skills; Experiential Learning; Islamic Education